2013
DOI: 10.1016/j.neurobiolaging.2013.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Variants in triggering receptor expressed on myeloid cells 2 are associated with both behavioral variant frontotemporal lobar degeneration and Alzheimer's disease

Abstract: Recent evidence suggests that rare genetic variants within the TREM2 gene are associated with increased risk for Alzheimer’s disease. TREM2 mutations are the genetic basis for a condition characterized by polycystic lipomembranous osteodysplasia with sclerosing leukoencephalopathy (PLOSL) and an early-onset dementia syndrome. TREM2 is important in the phagocytosis of apoptotic neuronal cells by microglia in the brain. Loss of function might lead to an impaired clearance and accumulation of necrotic debris and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
109
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(117 citation statements)
references
References 32 publications
8
109
0
Order By: Relevance
“…The finding that TREM2 variants act as strong genetic risk factors for Alzheimer's disease and many other neurodegenerative diseases (Benitez, et al, 2013,Borroni, et al, 2014,Cady, et al, 2014,Giraldo, et al, 2013,Gonzalez Murcia, et al, 2013,R. Guerreiro, et al, 2013a,R.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding that TREM2 variants act as strong genetic risk factors for Alzheimer's disease and many other neurodegenerative diseases (Benitez, et al, 2013,Borroni, et al, 2014,Cady, et al, 2014,Giraldo, et al, 2013,Gonzalez Murcia, et al, 2013,R. Guerreiro, et al, 2013a,R.…”
Section: Discussionmentioning
confidence: 99%
“…These findings have spurred numerous studies addressing the association between TREM2 and AD and other neurodegenerative diseases. Although negatives have been reported (Jiao, et al, 2014,Miyashita, et al, 2014,Ruiz, et al, 2014,Yu, et al, 2014, the association between TREM2 variants and AD has been confirmed by most studies (Benitez, et al, 2013,Giraldo, et al, 2013,Gonzalez Murcia, et al, 2013,Luis, et al, 2014,Slattery, et al, 2014. Moreover, TREM2 variants were also found to be associated with frontotemporal dementia-like syndrome or FTD (Borroni, et al, 2014,R.…”
Section: Introductionmentioning
confidence: 90%
“…Recently, the missense TREM2-R47H mutation has been identified and validated as a risk variant for LOAD (6,7,11,(15)(16)(17)(18)(19). Although numerous studies have investigated the genetic link between TREM2 variants and neurodegenerative diseases, only two other studies have empirically tested the functional outcome of disease-associated mutations (23,51).…”
Section: Discussionmentioning
confidence: 99%
“…TREM2 mutations are associated with neurological disorders (Bird, 2013;Giraldo et al, 2013;Guerreiro et al, 2013;Luis et al, 2014), although it is not well known how TREM2 contributes to these diseases. We found in our current analyses that the AD-associated R47H variant of TREM2 has increased terminal glycosylation with complex oligosaccharides in the Golgi apparatus and decreased solubility.…”
Section: Discussionmentioning
confidence: 99%